(3Odjd GdfLGM ai GeJMGf (B+ As - (3gGdI GdWhjd(B.s; (3gGdI GdWhjd(B.s ((3MdH (B:s (3TYGY ddfTQ h GdYdhe(B,s, 2004)
(3jJfGhd GdcJGH GdHQeLjGJ h GdcgQHGA hhMOGJ GdJZPjI h OYeGLgRI GdONd h GdNQL , GdMhGSjH GdTNUjI h GdeMehdI(B.s
(3GdHQeLjGJ h GdcgQHGA hhMOGJ GdJZPjI (B.s
Keywords: (3GdHQeLjGJ(B.s